2018
DOI: 10.1021/acs.jpcb.7b12532
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Experimental and Computational Spectroscopic Study of Hexacyanoferrate Complexes in Water: From Infrared to X-ray Wavelengths

Abstract: We present a joint experimental and computational study of the hexacyanoferrate aqueous complexes at equilibrium in the 250 meV to 7.15 keV regime. The experiments and the computations include the vibrational spectroscopy of the cyanide ligands, the valence electronic absorption spectra, and Fe 1s core hole spectra using element-specific-resonant X-ray absorption and emission techniques. Density functional theory-based quantum mechanics/molecular mechanics molecular dynamics simulations are performed to genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 71 publications
4
62
0
Order By: Relevance
“…The high S e of the ethaline thermocell can be attributed to the large entropy difference, specifically solvation entropy, between [Fe(CN) 6 ] 3− and [Fe(CN) 6 ] 4− . [Fe(CN) 6 ] 4− has a higher surface charge density compared to that of [Fe(CN) 6 ] 3− , which further regulates the orientation of solvent molecules 4 , 23 , 24 . The solvation effect of these redox species was investigated by FT-IR spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high S e of the ethaline thermocell can be attributed to the large entropy difference, specifically solvation entropy, between [Fe(CN) 6 ] 3− and [Fe(CN) 6 ] 4− . [Fe(CN) 6 ] 4− has a higher surface charge density compared to that of [Fe(CN) 6 ] 3− , which further regulates the orientation of solvent molecules 4 , 23 , 24 . The solvation effect of these redox species was investigated by FT-IR spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[Fe(CN) 6 ] 4− shows a broader C≡N stretching vibration peak with a full width at half maximum (FWHM) of 22.5 cm −1 against [Fe(CN) 6 ] 3− with an FWHM of 9.8 cm −1 . The broader peak corresponds to more substantial structural heterogeneity in the solvation environment of [Fe(CN) 6 ] 4− , which is originated from the stronger hydrogen bond interaction between the solute and the solvent 23 , 24 . This enhanced interaction, in turn, leads to a tightly-packed solvation shell surrounding [Fe(CN) 6 ] 4− than that of [Fe(CN) 6 ] 3− .…”
Section: Resultsmentioning
confidence: 99%
“…We investigate the ferricyanide complex in water, which serves as a prototypical model system for the structure and spectroscopy of Fe( iii ) octahedral transition metal complexes. 38–40 We consider cavities with resonance frequencies in the UV/Vis and X-ray regimes and develop the formalism for signals involving non-Hermitian polariton Hamiltonians, which include cavity dissipation and exciton decay.…”
Section: Introductionmentioning
confidence: 99%
“…The study highlighted the importance of explicitly treating the solvent in quantum chemical simulations in order to ensure an accurate modeling of the electronic structure of iron cyanides. 15 Both studies particularly found a strong hydrogen-bonding interaction between protic solvents and the cyanide (CN – ) ligands, which impacts intramolecular covalency. More specifically, the hydrogen bond has been reported to withdraw charge from the CN – ligands, which is compensated for by a concomitant increase in π-backdonation.…”
Section: Introductionmentioning
confidence: 99%